Evaluating the Solvent Stark Effect from Temperature‐Dependent Solvatochromic Shifts of Anthracene. Issue 7 (28th February 2020) - Janz, Timais; Güterbock, Manuel; Müller, Fabian; Quick, Martin; Ioffe, Ilya N.; Bischoff, Florian A.; Kovalenko, Sergey A.
Abstract: The solvent Stark effect on the spectral shifts of anthracene is studied with temperature‐dependent solvatochromic measurements. The Stark contribution Δ v Stark to the absorption shift Δ v p in polar solvents is measured to be Δ v Stark =(53±35) cm −1, in reasonable agreement with dielectric continuum theory estimate of 28 cm −1, whereas the major shift Δ v p ∼300 cm −1 presumably originates from the solute quadrupole. We pay attention to the accurate correction of Δ v p for the nonpolar contribution that is crucial when the shifts are modest in magnitude. Abstract : The solvatochromic Stark shift from anthracene in polar solvents is determined, Δ v Stark =(53±35) cm −1 . It agrees with dielectric continuum theory estimate of 28 cm −1 . The temperature dependence allows one to isolate Δ v Stark from a much larger shift of ∼300 cm −1 usually observed for nondipolar solutes in polar solvents, which is presumably due to the solute quadrupole.